Forming a methodological approach to the management system of innovative activities at enterprises in conditions of economic development - Panchenko, Vladimir; Ivanova, Roksolana; Viunyk, Olha; Androshchuk, Ilona; Guk, Olga (Journal of Business Economics and Management, 2022)
The main purpose of the study is to form a methodological approach to the management system of innovative activities at enterprises in the context of their economic development. To achieve this purpose, a methodical approach was formed containing a certain set of methods, the main of which is the methodology of functional modeling and graphic representation – IDEF0. As a result, the main decompositions of our model were presented with the proposed ways to improve the management system of innovative activities at the enterprise, taking into account the main goals of economic development. Our study was presented in the work of several companies in Eastern Europe to identify its effectiveness and convenience. The flexibility of the model makes it possible to effectively apply it in the practical activities of many enterprises. The originality of the research results implies the application of the existing methodology in a new area for it, namely in the management system of innovative activities and innovative development of the enterprise. The study has several limitations, which are primarily related to the fact that, due to the conditions of the pandemic, its practical application took place exclusively at Ukrainian enterprises.